Evaluating efficacy of bacteriophage therapy against Staphylococcus aureus infections using a silkworm larval infection model. Issue 1 (6th August 2013) - Takemura‐Uchiyama, Iyo; Uchiyama, Jumpei; Kato, Shin‐ichiro; Inoue, Tetsuyoshi; Ujihara, Takako; Ohara, Naoya; Daibata, Masanori; Matsuzaki, Shigenobu
Abstract: Silkworm larva has recently been recognized as an alternative model animal for higher mammals to evaluate the effects of antibiotics. In this study, we examined the efficacy of the bacteriophage (phage) therapy, which harnesses phages as antibacterial agents, against Staphylococcus aureus infections, using the silkworm larval infection model. Two newly isolated staphylococcal phages, S25‐3 and S13′, were used as therapeutic phage candidates. They were assigned to two different lytic phage genera, Twort‐like and AHJD‐like viruses, based on their morphologies and the N‐terminal amino acid sequences of the major capsid proteins. Both had a broad host range and strong lytic activity and showed preservative quality. Administration of these phages alone caused no adverse effects in the silkworm larvae. Moreover, the viruses showed life‐prolonging effects in the silkworm larval infection model 10 min, 6 h, 12 h, and 24 h following infection. Such phage effects in the silkworm larval model were almost paralleled to the therapeutic efficacies in mouse models. These results suggest that phages S25‐3 and S13′ are eligible as therapeutic candidates and that the silkworm larval model is valid for the evaluation of phage therapy as well as mouse models.